Characterization and Preliminary Application of Phage Isolated From Listeria monocytogenes - Li, Tianhao; Zhao, Xuehui; Wang, Xuejian; Wang, Zijian; Tian, Changqing; Shi, Wenjing; Qi, Yumei; Wei, Huilin; Song, Chen; Xue, Huiwen; Gou, Huitian (Frontiers in Veterinary Science, 2022)
Listeria monocytogenes (LM) is one of the four major foodborne bacteria that cause bacteremia and meningitis. To explore the control of listeriosis with natural phages, we used the double-layer agar plate method to isolate LM from slaughterhouse sewage and designated LP8. The result of electron microscopy indicated that the phage belonged to the family of Myoviridae. Whole-genome sequencing indicated that the genome size of LP8 is 87,038 bp and contains 120 genes. Mice were infected with LM and treated with penicillin G sodium, LP8, and the combination of these two. From the levels of lymphocyte subsets (CD4+, CD8+), the expression of cytokines (TNF-α, IL1β, IL-10, and IFN-γ), observation of pathological changes in organs (heart, liver, spleen, kidney, and brain), and the bacterial load of the spleen, we concluded the therapeutic effect of LP8 against listeriosis and demonstrate the feasibility of a combined therapy to reduce the use of antibiotics. This provides a new avenue for the treatment of listeriosis.